A Case of Prolonged Catatonia Caused by Sjögren's Syndrome. (3rd November 2020) - Inagaki, Takahiko; Kudo, Kotaro; Kurimoto, Naoki; Aoki, Takashi; Kuriyama, Kenichi
Abstract : Sjögren's syndrome (SS) is a chronic autoimmune disorder, often associated with some neuropsychiatric symptoms as well as systemic lupus erythematosus. Although catatonia is frequently reported in patients with systemic lupus erythematosus, it has been rarely reported in patients with SS. Herein, we present a case of SS with catatonia effectively and safely treated with modified electroconvulsive therapy (ECT). A 58-year-old woman showed prolonged catatonia and depressive mood along with pathologically dried eye and mouth. Based on physical findings and blood tests, she was diagnosed with SS. Because of the presence of pressure sores, we were unable to perform lumbar puncture for the diagnosis of abacterial encephalitis. Alternatively, single-photon emission computed tomography of her brain revealed multifocal hypoperfused areas in the parietotemporal region. Consequently, we performed ECT for the treatment of catatonia comorbid with SS. Following 20 sessions of ECT, the catatonia was improved without obvious adverse effects. One week after the last ECT, elevated levels of interleukin-6 were identified in the cerebral fluid. After receiving steroid pulse therapy, she has not experienced catatonia for more than 5 years. SS can cause catatonia, and ECT is a safe and effective option for the treatment of catatonia with SS.